Alkaline Earth Metal Chelates of 3-Halolawsonemonoximes - Kanase, D.G.; Kadam, S.S.; Takale, S.T.; Kelkar, V.D. (Asian Journal of Chemistry, 2010)
Metal chelates of 3-halolawsonemonoximes with beryllium (II), magnesium (II), calcium (II), strontium (II) and barium (II) were synthesized. The structural investigations were carried out using infrared spectra and electronic spectra. The molecular composition of all the chelates corresponds to [ML2×(H2O)2] except for beryllium (II) chelate in which it is [ML(OH)]2×2H2O. A dimeric structure for tetrahedrally surrounded metal ion with bridging hydroxo group is proposed for beryllium (II) chelates, while trans-octahedral structure is suggested for all remaining chelates.